Mating Status Influences Cold Tolerance and Subsequent Reproduction in the Invasive Ladybird Harmonia axyridis - Facon, Benoit; Estoup, Arnaud; Hufbauer, Ruth A.; Foucaud, Julien; Tayeh, Ashraf (Frontiers in Ecology and Evolution, 2017)
Among arthropods, ability to survive cold conditions may be instrumental for species invading temperate or colder climatic zones. Cold tolerance can be influenced by multiple environmental and physiological factors. We experimentally investigated the effects of mating status (unmated, mated, or mated and reproductive) on cold tolerance of the invasive harlequin ladybird Harmonia axyridis and subsequent reproduction. We found that unmated adults survive cold better than mated ones. Among mated individuals, those that had not reproduced survived better than those that had reproduced. After cold stress, formerly unmated females were mated, and we evaluated ability to reproduce in females from all three treatments. Females that reproduced prior to cold stress were less likely to reproduce after cold stress than females from both other treatments. We discuss what these results mean for the proportion of unmated females in H. axyridis aggregates at overwintering sites. This study highlights the importance of investigating how physiological status can affect cold tolerance of invasive arthropods.